2008
DOI: 10.1111/j.1755-148x.2008.00481.x
|View full text |Cite
|
Sign up to set email alerts
|

The antidepressant sertraline downregulates Akt and has activity against melanoma cells

Abstract: Melanoma is a common malignancy which is poorly responsive to chemotherapy and radiation. One of the major reasons melanoma responds poorly to these modalities is constitutive expression of Akt, which protects against apoptosis. The antidepressant sertraline was found to be a potent cytotoxic agent against A375 human melanoma. To determine the mechanism by which sertraline kills melanoma cells, Western blot analysis of signaling molecules, including phosphorylated Akt, caspase 9 and phospho-p70 S6 kinase was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
50
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 29 publications
3
50
0
Order By: Relevance
“…John et al (12) reported that as the downstream of PI3K/Akt, hyperphosphorylation of FoxO3a induced over-activation of primordial follicules (8,26,28). As previous studies have systematically reported that maintaining optimal activities of PI3K/Akt signaling pathway is essential for normal ovarian function, which not only regulates the balance between survival and activation of primordial follicles, but also is vital for the proliferation and differentiation of GCs (26)(27)(28). These studies suggested that regulation of the optimal expression level of FoxO3a is important spatially and temporally during follicular development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…John et al (12) reported that as the downstream of PI3K/Akt, hyperphosphorylation of FoxO3a induced over-activation of primordial follicules (8,26,28). As previous studies have systematically reported that maintaining optimal activities of PI3K/Akt signaling pathway is essential for normal ovarian function, which not only regulates the balance between survival and activation of primordial follicles, but also is vital for the proliferation and differentiation of GCs (26)(27)(28). These studies suggested that regulation of the optimal expression level of FoxO3a is important spatially and temporally during follicular development.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have systematically reported that maintaining optimal activity of Akt serine/threonine kinase 1 (Akt) signaling is essential for normal ovarian function, which regulates the balance between survival and activation of primordial follicles, and also is important for proliferation and differentiation of GCs (26)(27)(28). FoxO3a is also a substrate of Akt, thus, the present study also examined the expression of Akt ovaries.…”
Section: Introductionmentioning
confidence: 99%
“…Being a member of the selective serotonin reuptake inhibitor class of anti-depressants, sertraline possesses Akt inhibitory activity and acts as a serotonin transporter antagonist. 126 Human melanoma cells treated with sertraline exhibited low pAkt and phosphorylated p70 S6 kinase activities. 126 In addition, sertraline treatment induced endoplasmic reticulum stress triggering cellular apoptosis.…”
mentioning
confidence: 99%
“…126 Human melanoma cells treated with sertraline exhibited low pAkt and phosphorylated p70 S6 kinase activities. 126 In addition, sertraline treatment induced endoplasmic reticulum stress triggering cellular apoptosis. In animals, intraperitoneal administration of 1 mg/day setraline inhibited xenografted A375 tumor development.…”
mentioning
confidence: 99%
See 1 more Smart Citation